Educational Management in Madrasah with Gender Perspective: A Systematic Literature Review Study - Amini Amini (Journal of Contemporary Gender and Child Studies, 2026)
This study aims to systematically review the literature on educational management in madrasah through a gender perspective, in order to identify policy gaps, institutional practices, and the implementation of gender equality in achieving Sustainable Development Goals (SDGs) 4 and 5. Employing a Systematic Literature Review (SLR) approach following the PRISMA protocol, this review analyzed 38 articles published between 2013 and 2024 from reputable international and national databases, including Scopus, Web of Science, SINTA, and Google Scholar. The findings reveal three main patterns: (1) gender representation gaps in madrasah leadership positions remain significant, with women occupying only 23–31% of structural positions; (2) the curriculum and organizational culture of madrasah are predominantly androcentric, although several progressive madrasah have implemented gender-responsive policies; and (3) government policy support through Ministry of Religious Affairs regulations remains at the normative level and has not been fully translated into managerial practice. The novelty of this study lies in its cross-contextual synthesis that bridges Islamic educational management perspectives with global gender mainstreaming frameworks. The implications underscore the need for madrasah governance reform that explicitly integrates gender perspectives into institutional planning, organizing, and evaluation.